T1 mapping and major cardiovascular events in non‐ischaemic dilated cardiomyopathy: a systematic review and meta‐analysis - Federico Marchini; Beatrice Dal Passo; Gianluca Campo; Elisabetta Tonet; Matteo Serenelli; Alberto Cossu; Serena Chiarello; Maria Lo Monaco; Erika Bertella; Rita Pavasini (ESC Heart Failure, 2025)
Abstract Aims The aim of this study is to investigate the prognostic role of T1 mapping techniques in predicting major adverse cardiovascular events (MACE) in patients affected by non‐ischaemic dilated cardiomyopathy (NIDCM) by performing a meta‐analysis of available studies. Methods and results Data from 12 observational studies exploring the prognostic role of native T1 mapping and extracellular volume (ECV) were analysed with random effect generic inverse variance. The primary endpoint was MACE defined as a composite of heart failure or arrhythmic‐related events, expressed as hazard ratio (HR) with 95% confidence interval (CI). Secondary main outcomes were heart failure‐related events, arrhythmic‐related events, and weighted mean difference of native T1 mapping values or ECVs between patients with or without MACE. Overall, 4025 patients with NIDCM were included. The median follow‐up length was 22 (IQR 14–22) months. The primary outcome of MACE occurred in 610 patients with a pooled HR for native T1 mapping values of 1.07 (95% CI 1.04–1.09, I2 31.5%) and a pooled HR for ECV of 1.37 (95% CI 1.29–1.44, I2 0%). HF‐related events occurred in 492 patients, with a pooled HR for T1 mapping of 1.05 (95% CI 1.03–1.07, I2 1%) and a pooled HR for ECVs of 1.43 (95% CI 1.25–1.61, I2 63%). Arrhythmic‐related events occurred in 118 patients, with a pooled HR for T1 mapping values of 1.09 (95% CI 1.07–1.12, I2 0%). The weighted mean difference of native T1 mapping between patients with and without MACE was 30.91 (95% CI 18.45–43.16, I2 16.72%), while the mean difference of ECV was 4.52 (95% CI 2.78–6.26, I2 86%). Conclusions In NIDCM patients, native T1 mapping and ECV were associated with increased risk of the composite primary endpoint of MACE and the secondary endpoint of heart failure and arrhythmic‐related events.